APAKAH KPH DAPAT MEMPERBAIKI TATA KELOLA HUTAN INDONESIA? - Suwarno, Eno (Wahana Forestra: Jurnal Kehutanan, 2015)
Since the early 2000s, Forestry Department of Indonesia has been implementing the Forest Management Unit (FMU) development program. The existence of FMU can be seen as a prerequisite for the implementation of sustainable forest management and equitable. How FMU institution prospects can improve forest governance in Indonesia? The aim of this study is to explore the prospects of FMU institution to improve forest governance in Indonesia. The study used forestry governance dimensions of Mayers and Macqueen (2002) as an analytical tool. The study results showed that both conceptual and is based on the processes of development, FMU has accommodated most of the values of good forestry governance.